Characterization of a non-nudix pyrophosphatase points to interplay between flavin and NAD(H) homeostasis in Saccharomyces cerevisiae. - Joseph H Lynch; Na Sa; Sompop Saeheng; Nadia Raffaelli; Sanja Roje (PLoS ONE)
The flavin cofactors FMN and FAD are required for a wide variety of biological processes, however, little is known about their metabolism. Here, we report the cloning and biochemical characterization of the Saccharomyces cerevisiae pyrophosphatase Fpy1p. Genetic and functional studies suggest that Fpy1p may play a key role in flavin metabolism and is the first-reported non-Nudix superfamily enzyme to display FAD pyrophosphatase activity. Characterization of mutant yeast strains found that deletion of fpy1 counteracts the adverse effects that are caused by deletion of flx1, a known mitochondrial FAD transporter. We show that Fpy1p is capable of hydrolyzing FAD, NAD(H), and ADP-ribose. The enzymatic activity of Fpy1p is dependent upon the presence of K+ and divalent metal cations, with similar kinetic parameters to those that have been reported for Nudix FAD pyrophosphatases. In addition, we report that the deletion of fpy1 intensifies the FMN-dependence of null mutants of the riboflavin kinase Fmn1p, demonstrate that fpy1 mutation abolishes the decreased fitness resulting from the deletion of the flx1 ORF, and offer a possible mechanism for the genetic interplay between fpy1, flx1 and fmn1.